Kredibilitas Sarana dan Prasarana di MAN 1 Kulon Progo - Farid Setiawan; Muhammad Rizky Nur Risam; Lesta Yahsa Giardi; Hening Kusumaningrum (Program Studi Manajemen Pendidikan Islam Institut Agama Islam Sunan Kalijogo Malang, 2021)
This research is used to identify and understand the infrastructure planning system, inventory system, utilization or utilization system, maintenance system, and managerial impact of infrastructure facilities for teaching and learning activities at MAN 1 Kulonprogo. The basis of this research is descriptive analytical qualitative method, in which the data collection is in the form of an interview approach. The resource persons were obtained from the head of the Sarpras MAN 1 Kulonprogo department. The results of the study indicate that the effectiveness of learning is influenced by the fulfillment of learning and education infrastructures in schools. The management of facilities and infrastructure at MAN 1 Kulonprogo has been running effectively. The task of Facilities and Infrastructure is to assist school principals in carrying out school activities, especially those related to the activities of providing daily facilities and infrastructure, arranging planning, maintenance, implementation of teaching and learning activities related to facilities and infrastructure. Strive for all school facilities and infrastructure needs, plan for school facilities and infrastructure needs in one year, coordinate the utilization of permanent infrastructure facilities, Manage financing or budgets, both DIPA budgets and BOS budgets, make the types of reports that have been carried out in one year. Of course management of this infrastructure includes several aspects such as planning, inventory, utilization, use, and maintenance. The impact of a good infrastructure management system is that it raises the level of learning effectiveness that has increased, this is evidenced by student learning outcomes that are increasing as long as there is a good infrastructure management system.